2007
DOI: 10.1002/ajim.20436
|View full text |Cite
|
Sign up to set email alerts
|

Intrapulmonary lymph nodes in South African miners—an autopsy survey

Abstract: IPLNs are not uncommon among dust-exposed individuals. Silicotic fibrosis of IPLNs appears to precede pulmonary parenchymal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 11 publications
(17 reference statements)
0
11
0
Order By: Relevance
“…Some of these guidelines also describe the entity of benign intrapulmonary lymph nodes (IPLNs), for which further follow-up or investigation is not recommended (3,4,6). Over the past 3 decades, increasing numbers of studies have pathologically confirmed that some pulmonary nodules seen at CT are IPLNs (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). An autopsy survey of 2337 South African miners revealed an IPLN prevalence of 3.7%, although this was considered a minimum estimate (16).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Some of these guidelines also describe the entity of benign intrapulmonary lymph nodes (IPLNs), for which further follow-up or investigation is not recommended (3,4,6). Over the past 3 decades, increasing numbers of studies have pathologically confirmed that some pulmonary nodules seen at CT are IPLNs (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). An autopsy survey of 2337 South African miners revealed an IPLN prevalence of 3.7%, although this was considered a minimum estimate (16).…”
mentioning
confidence: 99%
“…Over the past 3 decades, increasing numbers of studies have pathologically confirmed that some pulmonary nodules seen at CT are IPLNs (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17). An autopsy survey of 2337 South African miners revealed an IPLN prevalence of 3.7%, although this was considered a minimum estimate (16). CT studies have also demonstrated the negligible risk of malignancy in nodules typical for IPLNs.…”
mentioning
confidence: 99%
“…3,4 There is evidence that lymph node silicosis precedes lung silicosis. [5][6][7][8] Further, if silicosis occurs only in the lymph nodes, the clearance by macrophages might have been effective but only under low exposure levels. We therefore investigated the relative occurrence of silicosis by site (lung or lymph nodes only) and in association with exposure to quartz dust in German uranium miners with lung cancer.…”
Section: Commentmentioning
confidence: 99%
“…The study base is 14 times larger than that of the former feasibility study 10,11 and almost twice as large as a study in South African miners. 5 Whereas in the feasibility study the slides of lung and non-lung cancer cases were sent to the United States and were each examined independently by 4 pathologists, in our study only lung cancer cases were examined and evaluated independently by 3 German pathologists. Accordingly, differences in the histopathology analysis protocols exist.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation